Implementasi Asesmen Diagnostik Non-Kognitif Gaya Belajar terhadap Pembelajaran Bahasa Indonesia di Kelas X-5 SMA Negeri 3 Selong - Yulia Ningsih; Baiq Rismarini Nursaly; Ahmad Sirajudin (Mataram University, 2026)
This study aims to describe the implementation of noncognitive diagnostic assessment of learning styles in Indonesian language learning in order to support learning in accordance with the characteristics of learners. The implementation of noncognitive diagnostic assessment in Indonesian language learning at the high school level is still relatively limited reported in previous studies, especially those that focus on mapping the learning styles of learners as the basis of learning design. This study uses descriptive qualitative methods supported by quantitative data. Subjects were 35 students of Class X-5 SMA Negeri 3 Selong. Data were obtained through noncognitive diagnostic assessment questionnaires, observations, interviews, and documentation, and then analyzed using the Miles & Huberman (1992) model which includes data reduction, data presentation, and conclusion. The results showed that 10 learners (28.6%) had a visual learning style, 8 learners (22.9%) had an auditory learning style, and 17 learners (48.5%) had a kinesthetic learning style. The mapping results become the basis for teachers in designing differentiated learning through the use of visual media, discussions, presentations, simulations, hands-on practice, and project-based learning. The implementation of non-cognitive diagnostic assessments helps teachers adjust learning strategies to the characteristics of learners so that Indonesian learning becomes more adaptive, increases activeness and motivation to learn, and supports the development of learners language skills.